2021
DOI: 10.2147/cmar.s287466
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Data on Osimertinib in Chinese Patients with Pretreated, EGFR T790M Mutation Positive, Advanced Non-Small Cell Lung Cancer: A Retrospective Study

Abstract: Purpose As a third-generation EGFR TKI has been taken orally, Osimertinib effectively inhibits mutant EGFR, including T790M EGFR resistance mutations. Here, we examined real-world efficacy and tolerability of Osimertinib among Chinese patients with advanced EGFR T790M-mutant NSCLC. Patients and Methods A total of 106 advanced NSCLC patients who were taking Osimertinib following disease progression after EGFR-TKIs or other treatments were retrospectively recruited in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In this context, the survival outcomes of other real-life studies varied between median 9.4 and 14.5 months of PFS, in the second-line treatment of advanced NSCLC with T790M mutation (9)(10)(11)(12)(13)(14). The Spanish Lung Cancer Group reported a median of 9.4 months PFS in 155 patients, and this was a very close to the PFS reported in the pivotal phase 3 trial (6, 10).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In this context, the survival outcomes of other real-life studies varied between median 9.4 and 14.5 months of PFS, in the second-line treatment of advanced NSCLC with T790M mutation (9)(10)(11)(12)(13)(14). The Spanish Lung Cancer Group reported a median of 9.4 months PFS in 155 patients, and this was a very close to the PFS reported in the pivotal phase 3 trial (6, 10).…”
Section: Discussionsupporting
confidence: 51%
“…The Spanish Lung Cancer Group reported a median of 9.4 months PFS in 155 patients, and this was a very close to the PFS reported in the pivotal phase 3 trial (6, 10). Other studies from different regions and ethnicities like China, Japan, France, and Poland demonstrated slightly better real-life outcomes than the AURA3 trial with approximately median 11-14 months of PFS (9,(11)(12)(13)(14). In general, outcomes of reallife experiences with the different classes of drugs just like cytotoxic chemotherapy, barely exceed the success of pivotal studies.…”
Section: Discussionmentioning
confidence: 91%
“…Intriguingly, osimertinib showed similar mPFS and mOS in T790M‐positive patients detected by first or repeat rebiopsy. Previous certain studies showed that osimertinib has comparable mPFS and mOS in pretreated advanced NSCLC with T790M mutation patients independently of previous treatment lines, but it was unclear which rebiopsy detected EGFR T790M mutation, and the patients treated by chemotherapy in the first line were included 23,24 . Though a study demonstrated that osimertinib would produce similar mPFS regardless of the timing of T790M detection, it remained unclear whether the patients make similar mOS, and treatments before osimertinib were not clear 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite osimertinib being the treatment of choice for EGFR T790M‐positive NSCLC, the pattern of osimertinib resistance and the appropriate subsequent treatment guidelines are limited in the real‐world setting. 14 , 15 , 16 , 17 , 18 This study aimed to determine the effective treatment direction after osimertinib administration by analyzing the pattern of PD in patients with NSCLC who were treated with osimertinib after first‐line EGFR‐TKI therapy.…”
Section: Introductionmentioning
confidence: 99%